2017
DOI: 10.1177/2309499017717179
|View full text |Cite
|
Sign up to set email alerts
|

Posterior hip approach yields better functional results vis-à-vis anterolateral approach in total hip arthroplasty for patients with severe hip dysplasia: A prospective randomized controlled clinical study

Abstract: THR surgery for patients with severe developmental dysplasia of hip is a challenging procedure, and posterior approach provides better functional outcomes regarding gait and AMSs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Little information is available in the literature on the role of bone geometry (fem-or al offset, acetabulum anteversion, neck-shaft angle) in the choice of surgical approach, even though some authors have highlighted the advantage of some approaches for specific pathologies, such as hip dysplasia. 43 Unfortunately, because of the sample size in our study, we were not able to conduct subgroup analyses looking at the impact of surgical approach with respect to specific patient characteristics such as sex, age or BMI. Finally, the ceiling effect common to the PROMs could conceal some improvements when patients score well at baseline, which makes it more difficult to measure the effect of the THR as a treatment for osteoarthritis in some cases.…”
Section: E185mentioning
confidence: 98%
“…Little information is available in the literature on the role of bone geometry (fem-or al offset, acetabulum anteversion, neck-shaft angle) in the choice of surgical approach, even though some authors have highlighted the advantage of some approaches for specific pathologies, such as hip dysplasia. 43 Unfortunately, because of the sample size in our study, we were not able to conduct subgroup analyses looking at the impact of surgical approach with respect to specific patient characteristics such as sex, age or BMI. Finally, the ceiling effect common to the PROMs could conceal some improvements when patients score well at baseline, which makes it more difficult to measure the effect of the THR as a treatment for osteoarthritis in some cases.…”
Section: E185mentioning
confidence: 98%
“…53 papers (72.6%) reported the term anterolateral approach to describe a complete intermuscular approach between the interval between GM and TFL 3,851 most of the authors were from European countries, but authors from north America were also present.…”
Section: Resultsmentioning
confidence: 99%
“…"We searched the Swedish Hip Arthroplasty to compare the posterior and anterolateral transgluteal approach" 13 Müller M et al 64 Arch Orthop Trauma Surg 2012. The direct lateral approach: impact on gait patterns, foot progression angle and pain in comparison with a minimally invasive anterolateral approach.…”
mentioning
confidence: 99%
“…While abductor mechanism dysfunction has most commonly been attributed to the direct incision or detachment of muscles in the lateral approach, other reasons like blunt trauma, retraction, denervation injury, and less common factors like thermal injury from polymethyl methacrylate can lead to damage to other muscles around the hip, including during modified or minimally invasive approaches 109,[115][116][117] . Despite this, our systematic review found a poor representation of muscle groups other than hip abductors in the comparative studies assessing strength changes following THA approaches 69,[71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][96][97][98][99][100][101][102][103][104][105][106][107][108][109] . It shows that despite persisting strength and functional abnormalities being reported following THA, not enough muscle strength data was found to compare different approaches or establish the superiority of one approach.…”
Section: Discussionmentioning
confidence: 99%
“…However, variations in measurement tools, methodology, and test positions used in THA research make the extrapolation of results and comparison of muscle strength outcomes complex. A variety of methods, including the Medical Research Council scale rating, manual muscle testing, handheld or isokinetic dynamometry, or other customized devices, has been used to quantify muscle strength in literature [51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85] . Substantial variability is also seen in the reporting of strength outcomes with the results expressed as raw numbers, values normalized to limb-length or the contralateral side, and strength or torque ratios to the non-operated side [51][52][53][54][55][56][57][58][59][60][61]…”
Section: Introductionmentioning
confidence: 99%